Transforming Malta Orchard into Agroforestry System with Different Crops for Improving Productivity, Profitability and Land Uses (Annals of Bangladesh Agriculture, 2021)
Sustainable agricultural practices like agroforestry systems are being advocated to overcome various problems of farming. A young malta (Citrus sinensis) orchard (3 years old) was transformed into a fruit tree-based agroforestry system in which the performances of summer (okra and Indian spinach) and autumn (mungbean and kangkong) crops and year-round spices (ginger and turmeric) were evaluated following randomized complete block design (RCBD) with three replication each and eventually compared between agroforestry systems and respective sole cropping (control) from March 2018 to February 2019 at BSMRAU field. The experimental results revealed that the yields of the associated crops deprived when grown at the closest row position from the bed of malta tree and spices. Yields of okra, Indian spinach, mungbean, kangkong, turmeric and ginger were reduced by 7.57, 6.52, 14.86, 13.26, 9.70 and 16.23%, respectively under agroforestry system as compared to control. However, malta yield was increased by 5.35% in agroforestry system than control trees. The findings also indicated that the crops in agroforestry system was less hindered by the shade effect of malta trees due to less dense canopy of young malta trees. In comparison to sole cropping system, the higher benefit-cost ratio (BCR) (2.93) and land equivalent ratio (LER) (2.83) were obtained in the studied agroforestry system that explicated higher system productivity and land uses. Notable improvement of total nitrogen and organic matter were obtained in the soil under agroforestry system. Therefore, malta-based agroforestry system can be a promising alternative to provide higher economic benefits, boosting food and nutritional security, improving soil nutrient status and utilization of land.Ann. Bangladesh Agric. (2020) 24(1) : 113-125